Neolithic Childhood. : Art in a False Present c.1930. - Franke, Anselm; Scherer, Bernd; Holert, Tom; Einstein, Carl; Nachtigall, Jenny; Zeidler, Sebastian; Stavrinka, Maria; Stakemeier, Kerstin; Albers, Irene; Lütticken, Sven; Eidelpes, Rosa; Marchini, Chiara; et al. (Berlin : Diaphanes, 2018)
Einstein, Carl ; Arp, Jean ; Sidibé, Kalifala ; Brassaï ; Levitt, Helen ; Van den berghe, Frits ; Ubac, Raoul ; Höch, Hannah ; Cahun, Claude ; Krull, Germaine ; Masson, André ; Toyen ; Léger, Fernand ; Oelze, Richard ; Ernst, Max ; Baumeister, Willi ; Wols ; von Moos, Max ; Paalen, Wolfgang ; Klee, Paul ; Yarrow, Catherine ; Roux, Gaston-Louis ; Gonzalez, Julio ; Miro, Joan ; Henri, Florence ; Nikritin, Solomon ; Lotar, Eli ; Styrsky, Jindrich ; Vézelay, Paule ; Eisenstein, Sergei ; Dulac, Germaine ; Hugo, valentine ; Yarrow, Catherine ; Povorina, Alexandra ; Hepworth, Barbara ; Renoir, Jean ; Allen, James L.
interbellum, avant-garde, surrealisme, primitivisme, modernisme , kunst en kapitalisme
Neolithic Childhood. Art in a False Present, c. 1930. Akademie der Künste, berlijn, 13 april tot 9 juli 2018
boek